2017
DOI: 10.5455/njppp.2017.7.0831714092017
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic effects of Cycas riuminiana leaf extracts on alloxan-induced diabetic ICR mice (Mus musculus L.)

Abstract: Background:The Philippines is one of the countries with high prevalence of diabetes mellitus. Although there are several drugs marketed to control it, there are unwanted side effects. Knowing this, alternative options have been sought for to control the disease. Aims and Objectives: To evaluate the effects of aqueous extracts of Cycas riuminiana on the blood glucose and cholesterol levels of alloxan-induced diabetic mice. Materials and Methods: Aqueous crude leaf extract from C. riuminiana was administered to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Laishram et al, reported that ethyl acetate fruit extract of Cycas pectinata Buch.-Ham exhibited alphaglucosidase inhibitory activity with an IC 50 value of (42.82 ± 0.039µg/ml) 17 . Leaf extract of C. riuminiana also showed antidiabetic potential by lowering the blood glucose level in alloxan-induced diabetic ICR mice 18 . Folklorically, powdered roasted whole seeds of pitogo are mixed with coconut oil and applied to wounds, boils and itchy skin lesions-likewise, cf.…”
Section: Discussionmentioning
confidence: 91%
“…Laishram et al, reported that ethyl acetate fruit extract of Cycas pectinata Buch.-Ham exhibited alphaglucosidase inhibitory activity with an IC 50 value of (42.82 ± 0.039µg/ml) 17 . Leaf extract of C. riuminiana also showed antidiabetic potential by lowering the blood glucose level in alloxan-induced diabetic ICR mice 18 . Folklorically, powdered roasted whole seeds of pitogo are mixed with coconut oil and applied to wounds, boils and itchy skin lesions-likewise, cf.…”
Section: Discussionmentioning
confidence: 91%